Not Just Endocarditis: Hospitalizations for Selected Invasive Infections Among Persons With Opioid and Stimulant Use Diagnoses—North Carolina, 2010–2018. (2nd September 2020) - Sredl, Megan; Fleischauer, Aaron T; Moore, Zack; Rosen, David L; Schranz, Asher J
Abstract: Background: While increases in overdoses, viral hepatitis, and endocarditis associated with drug use have been well-documented in North Carolina, the full scope of invasive drug-related infections (IDRIs) has not. We characterized trends in IDRIs among hospitalized patients in North Carolina. Methods: We compared invasive infections that were related or not related to drug use among hospitalized patients aged 18–55 years based on retrospective review of administrative records from 2010–2018. Hospitalizations for endocarditis, central nervous system/spine infections, osteomyelitis, and septic arthritis were labeled as IDRIs if discharge codes included opioid and/or amphetamine misuse. Trends, rates, and distributions were calculated. Results: Among 44 851 hospitalizations for the specified infections, 2830 (6.3%) were IDRIs. The proportion of infections attributable to drug use increased from 1.5% (2010) to 13.1% (2018), and the rate grew from 1.2 to 15.1 per 100 000. Compared with those who had non–drug-related infections, patients with IDRIs were younger (median age, 35 vs 46 years), more likely to be non-Hispanic white (81% vs 56%), and had longer hospitalizations (median, 8 vs 6 days). 43% of hospitalizations for IDRIs involved infective endocarditis. Conclusions: The rate of IDRIs in North Carolina increased substantially during 2010–2018, indicating an urgent need for enhanced infection prevention, harm reduction, and addiction services aimed at community and inpatient settings.